Effect of Arginine, Protamine, and Aqueous Extracts of Green Tea and Aloe Vera Against Enterococcus faecalis - Sanaz Najafi; Maryam Ghasempour; Abolfazl Davoodabadi; Sohrab Kazemi (Islamic Dental Association of Iran, 2019)
Background and Aim: Because of complexity in root canals, irrigating solutions are needed in addition to mechanical instrumentation for thorough cleansing of the root canal system. This in-vitro study was designed to determine the inhibitory effect of arginine, protamine, and aqueous extracts of green tea and aloe vera against Enterococcus faecalis (E. faecalis), which causes endodontic failure. Materials and Methods: In this experimental study, aqueous extracts of green tea and aloe vera and protamine at a concentration of 400 mg/ml and arginine at a concentra-tion of 160 mg/ml were used. E. faecalis was cultured on Mueller-Hinton broth, and minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the test materials against these microorganisms were determined using serial dilutions and according to the microdilution test. The positive control was 2.5% sodium hypochlorite (NaOCl). Results: Aqueous extract of aloe vera has high antibacterial activity against E. faecalis (MIC=12.5 mg/ml and MBC=100 mg/ml), and protamine had the least effect (MIC=400 mg/ml and MBC>400 mg/ml) compared to other test materials. NaOCl, with MIC and MBC of 0.25 mg/ml against E. faecalis, showed higher antibacterial activity compared to other test materials. Conclusion: Among the tested materials, except for NaOCl as a positive control, aqueous extract of aloe vera showed better antibacterial properties against E. faecalis.